Development of an index for measuring transparency of central banks - Bajalan, Saeed; Raei, Reza; Tehrani, Reza (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2012)
Although introducing explicit indices for measuring the transparency of central banks has enabled many empirical researches about theoretical issues of central banks’ transparencies, the simple and one-dimension definition of transparency behind many of these indices has raised doubts about their reliability. All of these indices explicitly or implicitly assume that making more information available or making more precise information would automatically lead to greater transparency. In other words, the fundamental presumption of all these indices is that there is no friction in the conveyance of information. In this paper, by applying the conceptual framework proposed by Winkler (2000), transparency has been defined as “the degree of genuine understanding of the monetary policy process and policy decisions by the public”. In accordance with such a definition, an index based on the four elements of Openness, Clarity, Honesty and Common Understanding has been developed to measure the transparency of central banks. Using the proposed index for measuring the transparency of three major central banks: the Federal Reserve, the ECB and the Bank of England and comparing the results with that of Siklos(2010) reveals that not only our calculated transparency’s score, but also our ranking is different from him. These two points highlight that central banks may find new ways of being transparent which could not be assessed just based on the openness on information, so the results of empirical studies conducted based on such indices could not be reliable.
Argumenta Oeconomica, 2012, Nr 1 (28), s. 13-40
Keywords: Central bank transparency index; openness; clarity; honesty; common understanding; banki centralne; wiarygodność informacji; przejrzystość